Detecting intermediate mass black holes in midiquasars with current and future surveys - Liodakis Iannis (OXFORD UNIV PRESS, 2022)
The lack of detected intermediate mass black holes poses a gap in our understanding of the growth and evolution of the most exotic of astrophysical objects. Here we investigate the possibility of low-luminosity relativistic jets launched by intermediate mass black holes in the centers of dwarf galaxies. We built population models that allow us to make predictions for their radio emission and quantify their detectability by current and future surveys. We find that the upcoming instruments in optical and radio like the SKA, ngVLA and the Vera C. Rubin Observatory will likely be able to detect a significant fraction (> 38%) of such sources population if they exist. In addition, our results suggest that it is not unlikely a small number of midiquasars possibly masquerading as low-luminosity active galactic nuclei may have already been detected by existing surveys.